2019
DOI: 10.24114/so.v2i2.11367
|View full text |Cite
|
Sign up to set email alerts
|

Efek Hepatoprotektif Minyak Buah Merah Pada Serum Tikus Dengan Aktifitas Fisik Maksimal

Abstract: Aktifitas fisik berat dapat mengakibatkan terjadi stress oksidatif yang berdampak kepada penurunan performance dan kesehatan atlet. Stres oksidatif dapat dicegah atau dikurangi dengan pemberian antioksidan. Salah satu sumber alami yang mengandung antioksidan adalah minyak buah merah (MBM). Sebagai antioksidan MBM diklaim mempunyai banyak khasiat tetapi semua efek ini masih perlu pembuktian secara ilmiah. Tujuan penelitian adalah untuk untuk melihat  pengaruh pemberian MBM terhadap kadar  Serum Glutamic Oxaloac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results showed that there was a difference in the mean number of leukocytes before and after maximum physical activity between the groups given red fruit oil and those not given red fruit oil, although statistically there was no significant difference. Based on the results of research conducted by Sinaga et al, (2018) concluded that administration of red fruit oil has a hepatoprotective effect in rats that perform maximum physical activity, meaning that the amount of oxidative stress that occurs due to maximum physical activity can be reduced through the administration of red fruit oil. functions as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that there was a difference in the mean number of leukocytes before and after maximum physical activity between the groups given red fruit oil and those not given red fruit oil, although statistically there was no significant difference. Based on the results of research conducted by Sinaga et al, (2018) concluded that administration of red fruit oil has a hepatoprotective effect in rats that perform maximum physical activity, meaning that the amount of oxidative stress that occurs due to maximum physical activity can be reduced through the administration of red fruit oil. functions as an antioxidant.…”
Section: Discussionmentioning
confidence: 99%